Polski proces Kafki. Wokół cenzorskiej recepcji utworów Franza Kafki i tzw. „czarnej literatury” - Mojsak, Kajetan (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article discusses the reception of Franz Kafka’s novels and the so-called “dark literature”, popular after 1956, by the censorship board. It presents the discussions around Kafka’s work and various interpretational strategies used to secure this literature a place in the culture of People’s Republic of Poland. The article presents analyses of the censors’ reviews of Kafka’s (but also Sartre’s or Faulkner’s) novels and offers insight into the censorship process and the literary life of the late 1950s in general.